An Analysis of Patent Application for TCM Intervention Treatment of Immune Diseases—Take China and Guangdong Province Patent as an Example. Issue 2 (October 2020) - Pang, Hongshen; Lin, Can; Qin, Xiaochu; Guo, Chen; Sun, Qi; Xu, Xiaoqi; Song, Yibing; Wang, Lu
Abstract: Immune diseases are a great threat to people's health. As a crucial component of Chinese medicine, TCM (Traditional Chinese Medicine) has many similarities with modern immune disease treatment in basic thinking and theory. Recently, it is found that TCM treatment has a positive effect on immune diseases treatment. To support the innovation and breakthrough of immune disease treatment, our paper focuses on the analysis of TCM intervention treatment of immune disease patents in China and Guangdong Province, respectively. It makes early warnings about patent risk management. Through the analysis, we figured out that there were three features in common: (1)the quantity of patent application in this area rose swiftly since 2013; (2) the main category of patent technology were concentrated on A61K36 group; (3) corporations and institutions were dominated applicants;(4) In China, the applicants were geographically centralized in Shandong, Beijing, Jiangsu; In Guangdong, the applicants generally assembled in Guangzhou, Dongguan, Foshan. In conclusion, there is a lack of core patents in this field. From the perspective of patent layout, Guangdong needs to increase foreign patent applications and develop more core patents to enhance its competitiveness in TCM intervention treatment of immune diseases.